Range‐wide persistence of the endangered arroyo toad (Anaxyrus californicus) for 20+ years following a prolonged drought. Issue 4 (19th April 2022) - Hitchcock, Cynthia J.; Gallegos, Elizabeth A.; Backlin, Adam R.; Barabe, Russell; Bloom, Peter H.; Boss, Kimberly; Brehme, Cheryl S.; Brown, Christopher W.; Clark, Denise R.; Clark, Elizabeth R.; Cooper, Kevin; Donnell, Julie; et al.
Abstract: Prolonged drought due to climate change has negatively impacted amphibians in southern California, U.S.A. Due to the severity and length of the current drought, agencies and researchers had growing concern for the persistence of the arroyo toad ( Anaxyrus californicus ), an endangered endemic amphibian in this region. Range‐wide surveys for this species had not been conducted for at least 20 years. In 2017–2020, we conducted collaborative surveys for arroyo toads at historical locations. We surveyed 88 of the 115 total sites having historical records and confirmed that the arroyo toad is currently extant in at least 61 of 88 sites and 20 of 25 historically occupied watersheds. We did not detect toads at almost a third of the surveyed sites but did detect toads at 18 of 19 specific sites delineated in the 1999 Recovery Plan to meet one of four downlisting criteria. Arroyo toads are estimated to live 7–8 years, making populations susceptible to prolonged drought. Drought is estimated to increase in frequency and duration with climate change. Mitigation strategies for drought impacts, invasive aquatic species, altered flow regimes, and other anthropogenic effects could be the most beneficial strategies for toad conservation and may also provide simultaneous benefits to several other native species that share the same habitat. Abstract : U.S. range‐wide surveys for arroyo toads were conducted at 100% of the historical watersheds and 76% of the historical sites following prolonged drought. Arroyo toads were detected at most sites delineated in the 1999 Recovery Plan for a downlisting consideration, yet toads could not be detected at 31% of sites surveyed indicating further declines. These are the most current and comprehensive data on number of extant arroyo toad populations since 1999 and can be used as a baseline for reevaluation of the Recovery Plan.